2022
DOI: 10.3390/ijms23158073
|View full text |Cite
|
Sign up to set email alerts
|

Leaf Bacteriome in Sugar Beet Shows Differential Response against Beet curly top virus during Resistant and Susceptible Interactions

Abstract: Beet curly top virus (BCTV) significantly reduces sugar beet yield in semi-arid production areas. Genetic resistance to BCTV is limited; therefore, identification of additional resistance-associated factors is highly desired. Using 16S rRNA sequencing and BCTV resistant (R) genotypes (KDH13, KDH4-9) along with a susceptible (S) genotype (KDH19-17), we investigated leaf bacteriome changes during BCTV post inoculation (pi). At day 6 (~6-week-old plants), Cyanobacteria were predominant (~90%); whereas, at week 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
(52 reference statements)
0
4
0
Order By: Relevance
“…These results indicated that PC1 can be referred to as the high-root weight component and the basis in the weighting of selection genotypes, thus PC1 is important to increase sugar beet productivity in the three environments. Alami et al [23], Islam et al [24], Majumdar et al [26] and Mehareb et al [40] have previously revealed similar results for the first two main PCs.…”
Section: Which-won-where Patternmentioning
confidence: 65%
See 1 more Smart Citation
“…These results indicated that PC1 can be referred to as the high-root weight component and the basis in the weighting of selection genotypes, thus PC1 is important to increase sugar beet productivity in the three environments. Alami et al [23], Islam et al [24], Majumdar et al [26] and Mehareb et al [40] have previously revealed similar results for the first two main PCs.…”
Section: Which-won-where Patternmentioning
confidence: 65%
“…[22], Alami et al [23], Islam et al [24], Kleuker and Hoffmann [25] and Majumdar et al [26]. The aim of this work was to study the effect of environment on genotypes of sugar beet under various regions in Egypt, and evaluate the magnitude of genotype x environment interaction using the multivariate methods, thus discovering the most stable sugar beet genotype and determining associations for the studied traits in ten sugar beet genotypes under three different environments.…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that most plant-beneficial bacteria detected on various plant-based media could not be detected by metabarcoding. The microbiome of the sugar beet has previously been analyzed using metabarcoding from various aspects: seasonal shifts in the lateral root microbiome [ 6 ], spatiotemporal changes in endophytic bacterial diversity [ 34 ], the rhizobiome of the sugar beet under different fertilizer systems [ 35 ], the leaf bacteriome in relation to the susceptibility of the sugar beet to beet curly top virus [ 36 ], and Cercospora leaf spot disease [ 37 ]. In this study, the microbiome of the sugar beet was investigated in two plant parts, the root and the leaf, and compared in different plant development stages (May, July, and October).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding pathogens and pests in plant biotic interactions, four of the papers in this issue focus on how plants recognize (shape the associated microbiomes) and defend against pathogens. Majumdar et al (2022a) [ 10 ] uncover, for the first time, the sugar beet leaf bacteriome response against beet curly top virus (BCTV). Using BCTV-susceptible and—resistant sugar beet genotypes and beet leafhopper (BLH)—mediated natural BCTV infection, their study highlights the restructuring of the bacterial microbiome in the leaves following BCTV infection, and their differential regulation in both sugar beet genotypes in a temporal manner of infection stage.…”
mentioning
confidence: 99%